Female labour force and child abuse in Malaysia using ARDL approach - Mohd Shahidan Shaari,; Nor Hidayah Harun,; Nor Ermawati Hussain, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Economic growth plays an important role in determining the number of female labour force. As economic growth intensifies, the number of female labour force increases simultaneously. However, the rise in the number of female labour force can lead to an increase in the number of child abuse cases. Therefore, this study is essential to explore the relationship between female labour force and child abuse cases in Malaysia. This study employs the ARDL bound testing approach and the results show that a higher number of female labour force can contribute to a higher child abuse case in Malaysia. Therefore, policies on female labour force should be formulated to cushion its effects on child abuse cases.